In Vitro Direct Shoot Organogenesis from Leaf Explants of Solanum nigrum (L.) – An Important Antiulcer Medicinal Plant - C. V. Naidu2*, T. M. Sridhar1 and (Journal of Phytology, 2011)
In the present study, a protocol for direct shoot organogenesis was developed from both field grown and in vitro derived leaf explants. The regeneration of shoots from leaf was found to vary with varying concentrations of BAP. The combination of BA (2.0 mg/L) and IAA (0.5 mg/L) produced maximum number of shoots (32.8) from leaf explants of field grown Solanum nigrum plants. Where as in in vitro derived leaf explants maximum number of shoots (38.0) was obtained on BA (3.0 mg/L) and IAA (0.5 mg/L) combination. All the in vitro raised shoots with a length of 3-5 cm were transferred to rooting medium supplemented with different concentrations of auxins such as IBA, NAA and IAA (0.25 – 1.0 mg/l). The best rooting response was observed on 0.5mg/l IBA. The well rooted plantlets were transferred to polybags containing soil + vermiculite in 1: 1 ratio for hardening. Finally the hardened plantlets were transferred to field conditions for maximum survivability. From the obtained results it is evident that leaf material is the best source for inducing maximum number of multiple shoots via direct shoot regeneration in Solanum nigrum plants.